Wear-resistant carbon fiber polyether-ether-ketone composite material and preparation method thereof

By using polydopamine-modified carbon fiber, inorganic filler and C8-C24 fatty acids in polyether ether eke ketone, the shortcomings of polyether ether eke composites in terms of mechanical properties and cold resistance are solved, and the wear resistance of the composites is achieved , improvement of mechanical properties and cold resistance.

CN119463452AActive Publication Date: 2025-02-18GUANGDONG ZHONGCHENG SPECIAL MATERIALS CO LTD

Patent Information

Application Number
CN202411365820.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Existing polyether ether ketone composites have shortcomings in mechanical properties and cold resistance, especially in terms of elongation of break and cold resistance.

Method used

Polydopamine modified carbon fiber, inorganic fillers (such as hydrotalc) and C8-C24 fatty acids were combined in polyether ether ketone to prepare composite materials with excellent mechanical properties, wear resistance and low temperature resistance through a molding process.

Benefits of technology

The composite material has achieved improvements in wear resistance and mechanical properties, while significantly improving its cold resistance, ensuring the stability and toughness of the material under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066181180000121
    Figure BDA0005066181180000121
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to an anti-wear carbon fiber polyether-ether-ketone composite material and a preparation method thereof. The composite material is prepared from the following raw materials in parts by weight: 70 to 80 parts of polyether-ether-ketone, 10 to 15 parts of polydopamine modified carbon fiber, 8 to 12 parts of inorganic filler and 0.1 to 1 part of C8-C24 fatty acid. The composite material provided by the invention has excellent mechanical properties and wear resistance, and also has excellent low temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an anti-wear carbon fiber polyetheretherketone composite material and a preparation method thereof. Background Art

[0002] Polyetheretherketone (PEEK) is a high-performance thermoplastic with excellent mechanical properties, chemical resistance, high temperature resistance and wear resistance. It has a wide range of applications in aerospace, automotive, electronics, medical and petrochemical industries. For example, its polyetheretherketone (PEEK) can be used to manufacture structural components inside mobile phones, such as connectors, frames and supports. Fiber is a high-strength, high-rigidity material favored for its light weight and excellent mechanical properties. Combining polyetheretherketone with carbon fiber can produce a composite material with excellent comprehensive properties.

[0003] In the existing preparation process of polyetheretherketone, it is often considered how to evenly distribute carbon fibers in the PEEK matrix to ensure that the performance of the composite material is uniform. The most commonly used method is to use a silane coupling agent or a titanate coupling agent to make the carbon fibers better increase the composite of the carbon fibers and the PEEK matrix. For example, in CN105504763B, potassium hexatitanate whiskers and four-needle zinc oxide whiskers are used for mixed reinforcement, which can greatly reduce the friction coefficient of the composite material while ensuring the mechanical properties of the composite material. At the same time, the addition of polytetrafluoroethylene can further reduce the friction coefficient, which is suitable for special environments such as high temperature, vacuum, radiation, and corrosion. Preparation method: Potassium hexatitanate whiskers are modified by titanate coupling agent, so that potassium hexatitanate whiskers and zinc oxide whiskers can be better dispersed in polyetheretherketone, solve the interface compatibility problem between existing whiskers and polyetheretherketone, and prepare a polyetheretherketone composite material with higher strength and better wear resistance; CN110922716B provides a PEEK composite material, which is made of zinc-aluminum alloy powder by smelting-nitrogen atomization method, and then obtains lamellar alloy powder by wet ball milling method, and then coated with graphene oxide to form a composite material with high thermal conductivity, high strength and microscopic small size effect. The composite material has excellent tribological and mechanical properties and can be applied to a variety of wear-resistant parts, such as sliders, bushings, etc. At the same time, the thermal conductivity of the composite material reaches up to 0.4387W / (m·K). Although the above technologies can improve the high temperature resistance and wear resistance of the polyetheretherketone composite material, in terms of mechanical properties, only the tensile strength of the polyetheretherketone composite material is significantly improved, and the improvement of its elongation at break is not obvious. Moreover, since polyetheretherketone is a semi-crystalline polymer, its cold resistance is poor. The above technologies cannot better solve the problem of cold resistance of composite materials.

[0004] Therefore, there is an urgent need for a wear-resistant carbon fiber polyetheretherketone composite material with excellent mechanical properties and cold resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a wear-resistant carbon fiber polyetheretherketone composite material and a preparation method thereof. The composite material has excellent mechanical properties and wear resistance, and also has excellent low-temperature resistance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In the first aspect, the present invention provides a wear-resistant carbon fiber polyetheretherketone composite material. The raw materials for preparing the composite material include, by weight: 70-80 parts of polyetheretherketone, 10-15 parts of polydopamine modified carbon fiber, 8-12 parts of inorganic filler, C8-C 24 Fatty acids 0.1-1 parts.

[0008] Furthermore, the raw materials for preparing the composite material include, by weight: 75 parts of polyetheretherketone, 12 parts of polydopamine modified carbon fiber, 10 parts of inorganic filler, and C8-C 24 0.4 parts of fatty acids.

[0009] Polyetheretherketone is a thermoplastic plastic. Furthermore, the polyetheretherketone is selected from polyetheretherketone A with a melt flow rate of 2-3 g / 10 min and polyetheretherketone B with a melt flow rate of 30-40 g / 10 min.

[0010] The melt flow rate in the present invention is measured under the conditions of 400° C. and 2.16 kg according to standard ASTM D1238.

[0011] Further, the polyetheretherketone is selected from polyetheretherketone A having a melt flow rate of 2.4 g / 10 min and polyetheretherketone B having a melt flow rate of 36 g / 10 min;

[0012] Furthermore, the mass ratio of polyetheretherketone A to polyetheretherketone B is 1:(2.2-4), for example, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.3, 1:3.5, 1:3.8, 1:4, and preferably 1:(2.5-3).

[0013] Furthermore, the polyetheretherketone A is in the form of particles; and the polyetheretherketone B is in the form of powder.

[0014] The polyetheretherketone A and polyetheretherketone B in the present invention can be obtained from the market. For example, the polyetheretherketone A is KT-820SL30, the model of the polyetheretherketone B is KT-880P.

[0015] In the present invention, the inventors found that in the system of the present invention, a combination of polyetheretherketones with different melt flow rates is used as a base material, which has an excellent balance of mechanical properties, heat resistance and processability, especially while improving the material strength, it can also ensure the overall toughness of the final composite material. The reasons for this may be: during the processing, the polyetheretherketone B with a higher melt flow rate can reduce the melt viscosity of the matrix resin, thereby improving the uniformity of the dispersion of the filler in the polyetheretherketone in the present invention, and at the same time, the polyetheretherketone A with a lower melt flow rate can act as a strength skeleton, thereby better increasing the strength. At the same time, the specific forms of polyetheretherketone A in particle form and polyetheretherketone B in powder form can also better make the system compatibility of the composite material better during preparation, which can further increase the comprehensive performance of the composite material.

[0016] Furthermore, the preparation method of the polydopamine modified carbon fiber comprises:

[0017] (1) mixing 2-4 mol / L dilute nitric acid with carbon fiber and reacting the mixture, filtering the mixture, washing the solid phase with water until it is neutral, and drying the mixture to a constant weight to obtain a carbon fiber intermediate;

[0018] (2) After the carbon fiber intermediate is mixed with water, Tris-HCl and dopamine hydrochloride are added to mix, and then ammonia water is added to adjust the pH value of the system to 9-12 for polymerization reaction, followed by centrifugation, and the solid phase is repeatedly washed with anhydrous ethanol and deionized water for 3-5 times, and finally vacuum dried to obtain polydopamine modified carbon fiber.

[0019] Furthermore, in step (1), 100 mL of dilute nitric acid contains 2-4 g of carbon fiber, preferably 3 g of carbon fiber; the diameter range of the carbon fiber is 5-10 μm, and the length range is 10-50 μm; the reaction conditions in step (1) include: reflux reaction at 80-90° C. for 2-4 hours.

[0020] The carbon fiber in the present invention can be obtained commercially, for example, from Beijing Chuanjing Carbon Fiber Company.

[0021] The washing and drying methods in step (1) are conventional methods in the art and will not be elaborated in detail in the present invention.

[0022] Further, in step (2): the mass ratio of the carbon fiber intermediate to water is 1: (1-2), for example, 1: 1, 1: 1.3, 1: 1.5, 1: 2, preferably 1: (1.2-1.5); the mass ratio of Tris-HCl to the carbon fiber intermediate is 1: (6-10), for example, 1: 6, 1: 7, 1: 8, 1: 9, 1: 10, preferably 1: (7-8); the mass ratio of dopamine hydrochloride to the carbon fiber intermediate is 1: (0.3-0.8), for example, 1: 0.3, 1: 0.4, 1: 0.5, 1: 0.6, 1: 0.7, 1: 0.8, preferably 1: (0.4-0.5);

[0023] Furthermore, in step (2), the polymerization reaction conditions include: reaction temperature of 45-55°C, reaction time of 18-24h; vacuum drying conditions include: drying in a vacuum drying oven at 60-70°C for 18-20h.

[0024] In step (2) of the present invention, the centrifugation method is a conventional method in the art and will not be elaborated here. The repeated washing with anhydrous ethanol and deionized water refers to washing with water after washing with anhydrous water, and the operation is repeated 3-5 times in total.

[0025] In the prior art, coupling agents are often used to increase the compatibility between carbon fiber and polyetheretherketone, but the addition of coupling agents has no obvious effect on the increase of mechanical properties, and most of the coupling agents are small molecules, which may also reduce the high temperature resistance of polyetheretherketone. In the present invention, polydopamine-modified carbon fiber is used to not only increase the wear resistance of the composite material, but also to a certain extent increase the mechanical properties of the composite material. This may be because the polydopamine on the surface of the carbon fiber in the polydopamine-modified carbon fiber has both internal lubrication and external lubrication. The internal lubrication effect enables the surface of the polydopamine-modified carbon fiber to penetrate between the polymer molecular chains like a plasticizer, thereby reducing the intermolecular force of the polyetheretherketone molecules, making the molecular chains easier to move and rotate, and at the same time enabling the polydopamine-modified carbon fiber to be better and more evenly interspersed in the polyetheretherketone; the external lubrication effect is that the polydopamine on the surface of the polydopamine-modified carbon fiber can better adsorb the friction surface and reduce the friction between the composite material and the device.

[0026] Furthermore, the inorganic filler is selected from at least one of zirconium oxide, hydrotalcite, aluminum oxide, calcium oxide and hollow glass microspheres, preferably hydrotalcite.

[0027] Furthermore, the average particle size of the hydrotalcite is 0.1-1 μm, preferably 0.6 μm.

[0028] The hydrotalcite in the present invention can be purchased from commercial sources, for example, from Kaisima (Dandong) High-tech Materials Technology Co., Ltd.

[0029] Furthermore, the C8-C 24 The fatty acid is selected from at least one of azelaic acid, oleic acid, stearic acid, myristic acid, arachidonic acid and docosahexaenoic acid, preferably arachidonic acid.

[0030] In the absence of inorganic fillers, especially hydrotalcite and C8-C 24 When fatty acids are added, the low temperature resistance of the composite material decreases significantly, which may be because polyetheretherketone B is conducive to the regular arrangement of polyetheretherketone chain segments, thereby promoting crystallization. The regular arrangement makes the internal chains of the composite material more easily broken at low temperatures. In the present invention, inorganic fillers, especially hydrotalcite and C8-C 24 Fatty acids can better increase the low temperature resistance of the composite material. On the one hand, this may be because the metal compound component in the hydrotalcite in the system of the present invention makes the composite material have better stability. On the other hand, this may be because C8-C 24 The long-chain molecules in fatty acids can be interspersed between the layered structures of hydrotalcite, making the hydrotalcite better dispersed in the system. 24 The long-chain molecules in fatty acids increase the interlayer spacing of hydrotalcite, and polyetheretherketone is in a glassy state at low temperatures. At this time, the hydrotalcite with an expanded layered structure can absorb more external energy and prevent the composite material from being destroyed.

[0031] In a second aspect, the present invention provides a method for preparing the wear-resistant carbon fiber polyetheretherketone composite material according to the first aspect of the present invention, the preparation method comprising: preparing polyetheretherketone, polydopamine modified carbon fiber, inorganic filler and C8-C 24 The fatty acids are mixed and then compression molded, and then cut and polished to obtain a carbon fiber polyetheretherketone composite material.

[0032] Furthermore, the mixing conditions include: a rotation speed of 22000-25000 rpm and a time of 12-30 s.

[0033] Furthermore, the compression molding conditions include: heating from 15-30°C to 380-405°C at a heating rate of 80-120°C / min, holding time of 15-30min at a pressure of 3-5MPa, and then cooling to room temperature at a cooling rate of 10-18°C / min.

[0034] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0035] 1. The use of polydopamine-modified carbon fiber and inorganic filler dispersed in polyetheretherketone in the present invention can better provide the wear resistance of the composite material and also better increase the mechanical properties of the composite material. This may be because the polydopamine on the surface of the polydopamine-modified carbon fiber can play a role in internal and external lubrication.

[0036] 2. In the specific system of the present invention, the inorganic filler and C8-C 24 The synergistic effect of fatty acids can overcome the defect of poor cold resistance of polyetheretherketone in the prior art, so that polyetheretherketone has excellent cold resistance. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment provides a wear-resistant carbon fiber polyetheretherketone composite material. The raw materials for preparing the composite material include, by weight: 75 parts of polyetheretherketone, 12 parts of polydopamine modified carbon fiber, 10 parts of inorganic filler, and C8-C 24 Fatty acid 0.4 part;

[0040] The polyetheretherketone is polyetheretherketone A with a melt flow rate of 2.4 g / 10 min and polyetheretherketone B with a melt flow rate of 36 g / 10 min; the mass ratio of polyetheretherketone A to polyetheretherketone B is 1:2.8; the model of polyetheretherketone A is KT-820SL30, in particle form; the model of polyetheretherketone B is KT-880P, in powder form;

[0041] The preparation method of polydopamine modified carbon fiber comprises: (1) mixing 3 mol / L dilute nitric acid with carbon fiber and reacting the mixture, filtering the mixture, washing the solid phase with water until it is neutral, and drying the mixture to a constant weight to obtain a carbon fiber intermediate; (2) uniformly mixing the carbon fiber intermediate with water, adding Tris-HCl and dopamine hydrochloride to mix the mixture, and then dropping ammonia water to adjust the pH value of the system to 10.4 to perform a polymerization reaction, centrifuging the mixture, repeatedly washing the solid phase with anhydrous ethanol and deionized water for 5 times, and finally vacuum drying the mixture to obtain the polydopamine modified carbon fiber;

[0042] In step (1), 3 g of carbon fiber is contained in 100 mL of dilute nitric acid; the diameter of the carbon fiber is in the range of 5-10 μm and the length is in the range of 10-50 μm, and it is purchased from Beijing Chuanjing Carbon Fiber Company; the reaction conditions are reflux reaction at 88° C. for 3 hours;

[0043] In step (2), the mass ratio of the carbon fiber intermediate to water is 1:1.4; the mass ratio of Tris-HCl to the carbon fiber intermediate is 1:7.5; the mass ratio of dopamine hydrochloride to the carbon fiber intermediate is 1:0.42; the polymerization reaction conditions are a reaction temperature of 48°C and a reaction time of 22h; the vacuum drying conditions are drying in a vacuum drying oven at 65°C for 20h;

[0044] The inorganic filler is hydrotalcite, the average particle size of the hydrotalcite is 0.6 μm, purchased from Kaisima (Dandong) High-tech Materials Technology Co., Ltd.

[0045] C8-C 24 The fatty acid is arachidonic acid;

[0046] The preparation method of the wear-resistant carbon fiber polyetheretherketone composite material comprises: mixing polyetheretherketone, polydopamine modified carbon fiber, inorganic filler and C8-C 24 The fatty acids are mixed and then molded, and then cut and polished to obtain a carbon fiber polyetheretherketone composite material;

[0047] The mixing conditions are: rotation speed of 24000 rpm, time of 20 s; the compression molding conditions are: heating from 18°C ​​to 400°C at a heating rate of 110°C / min, holding time of 20 min at a pressure of 4 MPa, and then cooling to room temperature at a cooling rate of 15°C / min.

[0048] Example 2

[0049] This embodiment provides a wear-resistant carbon fiber polyetheretherketone composite material. The raw materials for preparing the composite material include, by weight: 70 parts of polyetheretherketone, 15 parts of polydopamine modified carbon fiber, 12 parts of inorganic filler, and C8-C 24 Fatty acid 0.6 part;

[0050] The polyetheretherketone is polyetheretherketone A with a melt flow rate of 2.4 g / 10 min and polyetheretherketone B with a melt flow rate of 36 g / 10 min; the mass ratio of polyetheretherketone A to polyetheretherketone B is 1:3; the model of polyetheretherketone A is KT-820SL30, in particle form; the model of polyetheretherketone B is KT-880P is in powder form;

[0051] The preparation method of polydopamine modified carbon fiber comprises: (1) mixing 3 mol / L dilute nitric acid with carbon fiber and reacting the mixture, filtering the mixture, washing the solid phase with water until it is neutral, and drying the mixture to a constant weight to obtain a carbon fiber intermediate; (2) uniformly mixing the carbon fiber intermediate with water, adding Tris-HCl and dopamine hydrochloride to mix the mixture, and then dropping ammonia water to adjust the pH value of the system to 10.6 to perform a polymerization reaction, centrifuging the mixture, repeatedly washing the solid phase with anhydrous ethanol and deionized water for 5 times, and finally vacuum drying the mixture to obtain the polydopamine modified carbon fiber;

[0052] In step (1), 4 g of carbon fiber is contained in 100 mL of dilute nitric acid; the carbon fiber has a diameter range of 5-10 μm and a length range of 10-50 μm, and is purchased from Beijing Chuanjing Carbon Fiber Company; the reaction conditions are reflux reaction at 90° C. for 2 hours;

[0053] In step (2), the mass ratio of the carbon fiber intermediate to water is 1:1.5; the mass ratio of Tris-HCl to the carbon fiber intermediate is 1:8; the mass ratio of dopamine hydrochloride to the carbon fiber intermediate is 1:0.5; the polymerization reaction conditions are a reaction temperature of 55°C and a reaction time of 18h; the vacuum drying conditions are drying in a vacuum drying oven at 70°C for 20h;

[0054] The inorganic filler is hydrotalcite, the average particle size of the hydrotalcite is 0.6 μm, purchased from Kaisima (Dandong) High-tech Materials Technology Co., Ltd.

[0055] C8-C 24 The fatty acid is arachidonic acid;

[0056] The preparation method of the wear-resistant carbon fiber polyetheretherketone composite material comprises: mixing polyetheretherketone, polydopamine modified carbon fiber, inorganic filler and C8-C 24 The fatty acids are mixed and then molded, and then cut and polished to obtain a carbon fiber polyetheretherketone composite material;

[0057] The mixing conditions are: rotation speed of 23000 rpm, time of 30 s; the compression molding conditions are: heating from 22°C to 390°C at a heating rate of 100°C / min, at a pressure of 5 MPa, holding time of 22 min, and then cooling to room temperature at a cooling rate of 15°C / min.

[0058] Example 3

[0059] This embodiment provides a wear-resistant carbon fiber polyetheretherketone composite material. The raw materials for preparing the composite material include, by weight: 80 parts of polyetheretherketone, 10 parts of polydopamine modified carbon fiber, 8 parts of inorganic filler, and C8-C 24 0.3 parts of fatty acids;

[0060] The polyetheretherketone is polyetheretherketone A with a melt flow rate of 2.4 g / 10 min and polyetheretherketone B with a melt flow rate of 36 g / 10 min; the mass ratio of polyetheretherketone A to polyetheretherketone B is 1:2.5; the model of polyetheretherketone A is KT-820SL30, in particle form; the model of polyetheretherketone B is KT-880P, in powder form;

[0061] The preparation method of polydopamine modified carbon fiber comprises: (1) mixing 4 mol / L dilute nitric acid with carbon fiber and reacting the mixture, filtering the mixture, washing the solid phase with water until it is neutral, and drying the mixture to a constant weight to obtain a carbon fiber intermediate; (2) uniformly mixing the carbon fiber intermediate with water, adding Tris-HCl and dopamine hydrochloride to mix the mixture, and then dropping ammonia water to adjust the pH value of the system to 11 to perform a polymerization reaction, centrifuging the mixture, repeatedly washing the solid phase with anhydrous ethanol and deionized water for 5 times, and finally vacuum drying the mixture to obtain the polydopamine modified carbon fiber;

[0062] In step (1), 3 g of carbon fiber is contained in 100 mL of dilute nitric acid; the carbon fiber has a diameter range of 5-10 μm and a length range of 10-50 μm, and is purchased from Beijing Chuanjing Carbon Fiber Company; the reaction conditions are reflux reaction at 90° C. for 2 hours;

[0063] In step (2), the mass ratio of the carbon fiber intermediate to water is 1:1.2; the mass ratio of Tris-HCl to the carbon fiber intermediate is 1:7; the mass ratio of dopamine hydrochloride to the carbon fiber intermediate is 1:0.4; the polymerization reaction conditions are a reaction temperature of 55°C and a reaction time of 18h; the vacuum drying conditions are drying in a vacuum drying oven at 65°C for 18h;

[0064] The inorganic filler is hydrotalcite, the average particle size of the hydrotalcite is 0.6 μm, purchased from Kaisima (Dandong) High-tech Materials Technology Co., Ltd.

[0065] C8-C 24 The fatty acid is arachidonic acid;

[0066] The preparation method of the wear-resistant carbon fiber polyetheretherketone composite material comprises: mixing polyetheretherketone, polydopamine modified carbon fiber, inorganic filler and C8-C 24 The fatty acids are mixed and then molded, and then cut and polished to obtain a carbon fiber polyetheretherketone composite material;

[0067] The mixing conditions are: rotation speed of 22000 rpm, time of 30 s; the compression molding conditions are: heating from 20°C to 395°C at a heating rate of 120°C / min, at a pressure of 5 MPa, holding time of 25 min, and then cooling to room temperature at a cooling rate of 12°C / min.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 1 is:

[0070] The polyetheretherketone is polyetheretherketone B having a melt flow rate of 36 g / 10 min.

[0071] Comparative Example 2

[0072] The difference between this comparative example and Example 1 is:

[0073] The polyetheretherketone is polyetheretherketone A having a melt flow rate of 2.4 g / 10 min.

[0074] Comparative Example 3

[0075] This comparative example provides a wear-resistant carbon fiber polyetheretherketone composite material. The raw materials for preparing the composite material include, by weight: 75 parts of polyetheretherketone, 12 parts of carbon fiber, 10 parts of inorganic filler, C8-C 24 0.4 parts of fatty acid, 0.2 parts of titanate coupling agent NDZ-102;

[0076] Polyetheretherketone is the same as in Example 1; carbon fiber is the same as in Example 1; inorganic filler is the same as in Example 1; C8-C 24 Fatty acids are the same as in Example 1

[0077] The preparation method of the wear-resistant carbon fiber polyetheretherketone composite material comprises: mixing polyetheretherketone, carbon fiber, inorganic filler, C8-C 24 The fatty acid and the titanate coupling agent NDZ-102 are mixed and then compression molded, and then cut and polished to obtain a carbon fiber polyetheretherketone composite material;

[0078] The mixing conditions are: rotation speed of 24000 rpm, time of 20 s; the compression molding conditions are: heating from 18°C ​​to 400°C at a heating rate of 110°C / min, holding time of 20 min at a pressure of 4 MPa, and then cooling to room temperature at a cooling rate of 15°C / min.

[0079] Comparative Example 4

[0080] The difference between this comparative example and Example 1 is:

[0081] C8-C 24 The fatty acid was replaced by titanate coupling agent NDZ-102.

[0082] Comparative Example 5

[0083] The difference between this comparative example and Example 1 is:

[0084] The inorganic filler is 0 parts, and no inorganic filler is added when preparing the composite material.

[0085] Comparative Example 6

[0086] The difference between this comparative example and Example 1 is:

[0087] C8-C 24 The fatty acid is stearic acid.

[0088] Performance Testing

[0089] 1. The test standard for tensile strength is GB / T1040.2-2006.

[0090] 2. The test standard for elongation at break is GB / T1040.2-2006.

[0091] 3. The test standard for friction coefficient and wear scar width is GB / T 3960, and the test conditions are: 200N, 0.43m / s.

[0092] 4. Low temperature resistance test: Place the composite material in a -20°C environment for 18 hours, then test its tensile strength and elongation at break, and calculate the decrease rates of the tensile strength and elongation at break before placement.

[0093] The test results are shown in Table 1:

[0094] Table 1 Performance test results

[0095]

[0096] From the above performance test results, it can be seen that Examples 1-3 have mechanical properties and wear resistance, especially can simultaneously increase the tensile strength and elongation at break of the composite material, and also have excellent cold resistance, especially the comprehensive performance of Example 1 is the most outstanding. It is speculated that the polydopamine on the surface of the polydopamine-modified carbon fiber can play the role of internal and external lubrication, which may be because C 8- C 24The long-chain molecules in the fatty acid can interact with the inorganic filler, so that the inorganic filler is better dispersed in the system, and the inorganic filler can absorb more external energy to prevent the composite material from being destroyed; and the comparative example does not adopt the necessary technical solution, resulting in its corresponding performance test being significantly worse than the embodiment. In comparative example 1, only polyetheretherketone B with a high melt flow rate of 36g / 10min is used as the matrix, and it can be seen that the tensile strength and wear resistance of the composite material are slightly reduced, and the cold resistance and elongation at break are significantly reduced; in comparative example 2, only polyetheretherketone A with a low melt flow rate of 2.4g / 10min is used as the matrix, and it can be seen that the tensile strength and elongation at break of the composite material are significantly reduced, and the cold resistance, wear resistance and cold resistance are slightly reduced; in comparative example 3, unmodified carbon fiber is used as a filler, and a coupling agent is used to increase the compatibility of carbon fiber in the system. It can be seen that the tensile strength, elongation at break, wear resistance and cold resistance of the composite material are significantly reduced; in comparative example 4, C8-C 24 When the fatty acid is replaced by the titanate coupling agent NDZ-102, it can be seen that the tensile strength, elongation at break, wear resistance and cold resistance of the composite material are all reduced, especially the cold resistance is reduced significantly; in Comparative Example 5, no inorganic filler is used, and it can be seen that the tensile strength, elongation at break, wear resistance and cold resistance of the composite material are all reduced, especially the cold resistance is reduced significantly; in Comparative Example 5, C8-C 24 The fatty acid is stearic acid, and it can be seen that the tensile strength, elongation at break, wear resistance and cold resistance of the composite material are slightly reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0097] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A wear-resistant carbon fiber polyetheretherketone composite material, characterized in that: The raw materials for preparing the composite material include, by weight: 70-80 parts of polyetheretherketone, 10-15 parts of polydopamine modified carbon fiber, 8-12 parts of inorganic filler, C8-C 24 Fatty acids 0.1-1 parts.

2. The wear-resistant carbon fiber polyetheretherketone composite material according to claim 1, characterized in that: The polyetheretherketone is selected from polyetheretherketone A with a melt flow rate of 2-3 g / 10 min and polyetheretherketone B with a melt flow rate of 30-40 g / 10 min, wherein the melt flow rate is measured at 400° C. and 2.16 kg according to standard ASTM D1238.

3. The wear-resistant carbon fiber polyetheretherketone composite material according to claim 1, characterized in that: The preparation method of the polydopamine modified carbon fiber comprises: (1) mixing 2-4 mol / L dilute nitric acid with carbon fiber and reacting the mixture, filtering the mixture, washing the solid phase with water until it is neutral, and drying the mixture to a constant weight to obtain a carbon fiber intermediate; (2) After the carbon fiber intermediate is mixed with water, Tris-HCl and dopamine hydrochloride are added to mix, and then ammonia water is added to adjust the pH value of the system to 9-12 for polymerization reaction, followed by centrifugation, and the solid phase is repeatedly washed with anhydrous ethanol and deionized water for 3-5 times, and finally vacuum dried to obtain polydopamine modified carbon fiber.

4. The wear-resistant carbon fiber polyetheretherketone composite material according to claim 3, characterized in that: In step (1): 100 mL of dilute nitric acid contains 2-4 g of carbon fiber; the diameter of the carbon fiber ranges from 5 to 10 μm and the length ranges from 10 to 50 μm; the reaction conditions include: reflux reaction at 80 to 90° C. for 2 to 4 hours.

5. The wear-resistant carbon fiber polyetheretherketone composite material according to claim 3, characterized in that: In step (2): The mass ratio of the carbon fiber intermediate to water is 1:(1-2); the mass ratio of Tris-HCl to the carbon fiber intermediate is 1:(6-10); and the mass ratio of dopamine hydrochloride to the carbon fiber intermediate is 1:(0.3-0.8).

6. The wear-resistant carbon fiber polyetheretherketone composite material according to claim 3, characterized in that: In step (2): The conditions for the polymerization reaction include: a reaction temperature of 45-55° C. and a reaction time of 18-24 hours; the conditions for vacuum drying include: drying in a vacuum drying oven at 60-70° C. for 18-20 hours.

7. The wear-resistant carbon fiber polyetheretherketone composite material according to any one of claims 1 to 6, characterized in that: The inorganic filler is selected from at least one of zirconium oxide, hydrotalcite, aluminum oxide, calcium oxide and hollow glass microspheres.

8. The wear-resistant carbon fiber polyetheretherketone composite material according to claim 7, characterized in that: The C8-C 24 The fatty acid is selected from at least one of azelaic acid, oleic acid, stearic acid, myristic acid, arachidonic acid and docosahexaenoic acid.

9. A method for preparing the wear-resistant carbon fiber polyetheretherketone composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: mixing polyetheretherketone, polydopamine modified carbon fiber, inorganic filler and C8-C 24 The fatty acids are mixed and then compression molded, and then cut and polished to obtain a carbon fiber polyetheretherketone composite material.

10. The method for preparing the wear-resistant carbon fiber polyetheretherketone composite material according to claim 9, characterized in that: The mixing conditions include: a rotation speed of 22000-25000rpm and a time of 12-30s; the compression molding conditions include: heating from 15-30°C to 380-405°C at a heating rate of 80-120°C / min, at a pressure of 3-5MPa, a holding time of 15-30min, and then cooling to room temperature at a cooling rate of 10-18°C / min.

Citation Information

Patent Citations

  • Whisker-reinforced polyetheretherketone composites and their preparation methods

    CN105504763B

  • A polyetheretherketone composite material and its preparation method

    CN110922716B

  • Polyether ether ketone composite material and a preparation method and application thereof

    CN109851989A

  • Polyetheretherketone self-lubricating composite material as well as preparation method and application thereof

    CN109880288A

Cited By

  • Polyphenylene sulfide flame-retardant material for new energy automobile battery pack shell and preparation method of polyphenylene sulfide flame-retardant material

    CN120209576A